PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERINTEGRASI STEM TERHADAP HASIL BELAJAR IPA MATERI RANGKA MANUSIA DI MADRASAH IBTIDAIYAH - Muhammad Umar Wakhid; Agus Dwi Prasojo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning outcomes and problem-solving abilities of students in Natural Science (IPA), particularly regarding anatomical and conceptual topics such as the human skeletal system. The study aimed to analyze the significant impact of implementing the Problem-Based Learning (PBL) model integrated with the Science, Technology, Engineering, and Mathematics (STEM) approach on science learning outcomes concerning the human skeleton. This quantitative study employed a quasi-experimental design, specifically the non-equivalent control group design. It was conducted at MI Al-Fatah Sindang Anom during the odd semester of the 2026/2027 academic year. The study population comprised all Grade VI students; Class VI-A served as the experimental group (n=28) and Class VI-B as the control group (n=28), selected via purposive sampling. Data collection utilized a reasoned multiple-choice test with established validity and reliability. Data analysis involved prerequisite testing (Shapiro-Wilk normality and Levene’s homogeneity tests) followed by an independent sample t-test and N-Gain analysis. The results showed a t-test significance value of 0.000 (p < 0.05), indicating a significant difference in learning outcomes between the experimental and control groups. Improvements in learning outcomes were measured using N-Gain; the experimental group achieved a score of 0.72 (high category), whereas the control group scored 0.35 (medium category). It is concluded that the STEM-integrated PBL model is highly effective in enhancing science learning outcomes for Grade VI Madrasah Ibtidaiyah (MI) students regarding the human skeletal system. The study recommends that teachers adopt PBL-STEM as an innovative pedagogical alternative at the primary education level.